An improved method of Cr purification for high precision measurement of Cr isotopes by double spike MC-ICP-MS. Issue 5 (19th April 2018) - Zhu, Jian-Ming; Wu, Guangliang; Wang, Xiangli; Han, Guilin; Zhang, Lixin
Abstract : A flexible, easy and highly efficient Cr purification method was developed for high-precision measurement of Cr isotopes by double-spike MC-ICP-MS. Abstract : Chromium (Cr) isotopes have been used to trace pollution processes and reconstruct paleo-redox conditions. However, the precise determination of Cr isotopes is still challenged by difficulties in purifying Cr from samples with low Cr and high matrix content. Here, we developed an improved, flexible and easily operated three-step chromatographic procedure to separate Cr from high-matrix samples. A continuous, two-stage column (Step I) filled with 2 mL cation resin AG50W-X8 (200–400 m) and 2 mL anion resin AG1-X8 resin (100–200 m), followed by Step II, with 1 mL of AG1-X8 resin (200–400 m), was used to remove at least 99% of Ca, Fe, and Ti, and >90% of V and most other matrix elements, even for samples with Fe/Cr ≈ 6000 and Ti/Cr ≈ 1000. The recovery of Cr in both Step I and Step II can reach nearly 100%. Step III utilizes 2 mL AG1-X8 (100–200 m) combined with an (NH4 )2 S2 O8 oxidant to remove residual matrix elements and achieve high-purity Cr. The total yield of Cr through our three-step procedure is greater than 80% even for low-Cr (2.6 μg kg −1 ) samples. A relatively small sample amount (300–600 ng Cr) is enough to achieve high precision Cr isotope measurement due to a low procedural blank (<1 ng). Chromium isotopes in geological reference materials (BHVO-2, JDo-1, JP-1, etc. ) were measured on a Neptune Plus MC-ICP-MS. The long-term external precision is 0.06‰ (2SD), and the δ 53 Cr values are in great agreement with previously reported values. The δ 53 Cr of the upper continental crust is estimated to be −0.10 ± 0.10‰ using a suite of granite, diamictite, sediment and loess samples. Both plants and human hair are ∼0.1‰ heavier than the upper continental crust. Tests show that our improved purification procedure is applicable to various geological and environmental samples.